Two new species of Pseudophanias Raffray from Myanmar (Coleoptera: Staphylinidae: Pselaphinae) - Inoue, Shota; Nomura, Shûhei (Zootaxa, 2021)
Two new species of the genus Pseudophanias Raffray, P. spinicornis sp. nov. and P. tanintharyiensis sp. nov., are described as the first named species of the genus from Myanmar.